The status of doping and drug use and the implications for boxing - Wadler, G. I. (Clinics in Sports Medicine, 2009)
Boxers are not immune from the abuse of drugs. This article outlines the history of drug taking in boxing and sport in general. The current criteria that constitute doping, and prohibited substances and methods in and out of competition, according to guidelines issued by the World Anti-Doping Agency, are listed. Drugs and therapeutic exemptions are discussed